IMPLEMENTATION OF OBJECT MOVEMENT MONITORING SYSTEMS BASED ON LOW-FREQUENCY SURFACE SIGNALS - VANCHAK, VITALII; MELNYCHUK, STEPAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Geosignal monitoring utilizedas a crucial technological tool for observing and analyzing the stability, reliability, and safety in various areas of use, including transportation networks, construction projects, engineering structures. It is also widely used for securing perimeters, conducting geological research, and tracking changes in observed objects. This study focuses on the review of eight geosignal-based perimeter monitoring systems, which are designed to detect movement within a designated observation radius and classify objects based on the processing of geosignal data. The paper provides a detailed analysis of the operational principles of these systems, with an emphasis on their capabilities in object detection and classification, methods of transferring information, and accessibility for end users. Key system attributes, including detection range for different class of objects, distance of radio signal transmission and used frequency range, operational duration, dimensions, and weight, Furthermore, the study highlights the current challenges and limitations of existing geosignal monitoring technologies, such as the need for higher efficiency, while keeping compact size and long work duration, optimization of system data transferringsteps. Several promising directions for future research and development are proposed, including the improvement signal processing methods, development of more robust algorithms for geosignal interpretation, decrease of data transfer steps from geosignal monitoring devices to the end user. By addressing these issues, the potential of geosignal monitoring systems can be further improve their capability and usability, ensuring greater effectiveness, flexibility and adaptability in various environments. This comprehensive review offers insights into the current state of the technology and underscores its importance in advancing modern monitoring solutions.